THE ROLE OF TAX INCENTIVES ON THE RELATIONSHIP OF FACTORS AFFECTING TAX COMPLIANCE - Muhamad Safiq; Sultan Bhisri (Sekolah Tinggi Pariwisata Mataram, 2022)
At this time, the issue of tax compliance is an interesting topic to study, due to the decline in revenue vehicle tax in Bekasi City in 2021 even though the government has provided relief in the form of tax incentives. This happens because of a lack of awareness, moral obligation to the importance of paying taxes or it can also occur due to a lack of quality tax services and clear socialization to the community. This study aims to examine whether taxpayer awareness, taxpayer moral obligation, tax sanctions, tax socialization, and service quality affect taxpayer compliance with motorized vehicles moderated by tax incentives. This study uses a quantitative method with Google Forms to distribute questionnaires to respondents who are domiciled in Bekasi City. In this study, researchers obtained a sample of 242 respondents from a minimum sample of 200 respondents. Researchers used statistical analysis of Structural Equation Modeling (SEM) using the SmartPLS version 3.0 application. The results of this study indicate that tax awareness and tax sanctions have a positive and significant effect on tax compliance, while moral obligations, tax socialization and tax service quality do not affect tax compliance. Meanwhile, tax socialization moderated by tax incentives affects tax compliance positively and significantly. Meanwhile, tax awareness, moral obligation, service quality, tax sanctions do not affect tax compliance. In other words, tax compliance does not directly increase due to tax incentives. The limitations of this study are the lack of a large sample area and there are several other factors that can affect tax compliance, but are not included in the variables studied.